ISLAMIC EDUCATION REFORM: A Critical Study of the Renewal of Fazlur Rahman's Thought - Muhammad Rafiq Kurniawan (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2024)
According to Fazlur Rahman that Islamic education in countries where the majority of the population is Muslim, such as Turkey, Indonesia, Egypt and Pakistan, are still faced with educational problems, namely: (1) Educational goals are not directed towards positive goals. (2) The dichotomy of the education system (3) The low quality of students, the emergence of broken personalities and the absence of students who have a deep spiritual and intellectual commitment to Islam (4) It is difficult to find professional educators who have creative and integrated minds, (5) the lack of books available in the library. According to Fazlur Rahman, the contribution to the modernization of Islamic education includes five areas, namely (1) educational objectives (2) the dichotomy of the education system (3) students (4) educators, and (5) educational equipment. The psychological burden of Muslims facing the West has caused the goals of Islamic education not to be directed to positive goals. The purpose of Islamic education is oriented to the afterlife and is defensive in nature. To overcome this, according to Rahman, there are three efforts that must be made: (1) orienting the goals of Islamic education to the life of the world and the hereafter at the same time and sourced from the Qur'an. (2) eliminating the psychological burden of Muslims in facing the West, and (3) eliminating negative attitudes towards science.